PENGARUH CARBON EMISSION DISCLOSURE DAN ENVIRONMENTAL PERFORMANCE TERHADAP NILAI PERUSAHAAN - Khasanah, Uswatun; Anggraini, Desy Ismah (Income, 2024)
The biggest challenge facing the world community this century is climate change due to global warming caused by various human activities. Companies are required to demonstrate their involvement in environmental management to help achieve business sustainability. Most of the causes of climate change are the result of corporate industrial activities which cause greenhouse gas emissions to continue to increase. This research aims to test and analyze the influence of carbon emission disclosure and environmental performance on company value in the basic materials, industrial, and healthcare sectors listed on the IDX for the 2021-2022 period. This type of research is causal research with a quantitative approach. The sample in this study is 34 obtained from 17 companies in the basic materials, industrial, and healthcare sectors listed on the IDX with a research period of 2 years. The result show that carbon emission disclosure and environmental performance have a significant influence on company value both partially and simultaneously in companies in the basic materials, industrial, and healthcare sectors listed on the IDX for the 2021-2022 period. In this research, company value is proxied using PBV. It is hoped that future researchers can use other measurement indicators such as Tobins’Q and can maximize the number of samples and expand the research object.